Absorption and adsorption of benzene, toluene, and xylene from water using a hydrophobic polydimethylsiloxane foam - Alatawi, Lila Saleem E. (2024)
Due to untreated wastewater disposal from a growing population and industry, biological and chemical pollutants have accumulated in the environment. Benzene, toluene, and xylene (BTX) are among the most common pollutants in industrial wastewater. Due to their toxic and carcinogenic nature, BTX-containing industrial wastewater requires proper treatment prior to discharge to open water. The low adsorption capacity and low recyclability of the current sorbents have motivated the search for more efficient sorbent for BTX removal. In this study, polydimethylsiloxane (PDMS) foam was prepared and used to remove BTX from water. A facile and green synthesis was developed for the preparation of PDMS foam. Using the gas foaming method, PDMS was polymerized with the addition of NaHCO3 as a blowing agent and acetic acid as the catalyst. The prepared PDMS foams were characterised by their density, morphology (FESEM), hydrophobicity (water contact angle), and mechanical properties. By changing the NaHCO3: acetic acid ratios and the curing temperature, foams with varying properties were obtained. The PDMS foam produced at a 1: 2 NaHCO3: acetic acid ratio and cured at 100°C (1:2(100) foam) has the highest hydrophobicity of all the PDMS foams. All PDMS foams can be compressed to a maximum strain of 95% and retained their original size, showing excellent mechanical properties. With increasing curing temperatures, the porosity of the foams increases while their density, elastic modulus, and compressive strength decrease. However, the PDMS characteristics does not depend on the NaHCO3: acetic acid ratio, as no clear trend in feature change is observed with the changing of the NaHCO3: acetic acid ratio. The potential of the synthesised PDMS foams as sorbents to remove BTX from water was evaluated. The absorption of BTX by PDMS foams was studied at high BTX concentrations (higher than the solubility of BTX compounds in water). In contrast, the adsorption study was applied to remove low- concentration BTX when these organic compounds are dissolved in water. In the absorption method, the 1:2(100) PDMS foam exhibited the highest absorption capacity with 7.5 g/g, with 95% uptake occurring within the first minute, attributed to its higher hydrophobicity and medium porosity. The absorption capacity of PDMS foam followed the order: X>T>B. The PDMS foam retained its high absorption capacity for B, T, and X even after 10 absorption-desorption cycles, indicating its excellent stability and reusability. For the adsorption study, batch experiments were carried out for B, T, and X uptake from aqueous solution onto PDMS foam in mono-component systems at varied operating conditions. 1:2(100) PDMS foam was found to have the highest adsorption capacity with 4.2 mg/g at 50 mg/L of benzene concentration. BTX adsorption also increased with increasing concentration. The adsorption data were well-fitted with Freundlich isotherms and a pseudo-second-order kinetic model. The adsorption capacity of PDMS foam followed the order X>T>B. Based on experimental findings, PDMS foam is a promising sorbent with high stability and reusability for BTX removal from water.